2020
DOI: 10.1111/eip.12913
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative analysis of the Meals, Mindfulness, & Moving Forward (M3) lifestyle programme: Cultivating a ‘safe space’ to start on a ‘new path’ for youth with early episode psychosis

Abstract: Aim The Meals, Mindfulness, & Moving Forward (M3) programme included nutrition education, hands‐on cooking classes, mindfulness meditation practice, physical activities and facilitated group sharing. M3 was designed as a supplement to standard care for youths (age 15‐25 years) with first‐episode psychosis (FEP) who were clients of coordinated specialty care teams. M3's primary aim was feasibility by demonstrating high programme attendance; secondary aims included cardiometabolic measures. Data collection inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Quantitative Descriptive 75 41. (a) Usher et al [ 88 ] RCT NCT02398292 (b) Thompson et al [ 29 ] Qual USA Early intervention services Meals, mindfulness, and Moving forward M 3 , n = 17 ( n = 13 in qual study) TAU, n = 16 1 × 30 min session (within longer 4 h session with varied activities)/week for 12 weeks Attendance and participant experiences 3. Quantitative non-randomised 5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative Descriptive 75 41. (a) Usher et al [ 88 ] RCT NCT02398292 (b) Thompson et al [ 29 ] Qual USA Early intervention services Meals, mindfulness, and Moving forward M 3 , n = 17 ( n = 13 in qual study) TAU, n = 16 1 × 30 min session (within longer 4 h session with varied activities)/week for 12 weeks Attendance and participant experiences 3. Quantitative non-randomised 5.…”
Section: Resultsmentioning
confidence: 99%
“…We extracted qualitative data where available from the 11/43 studies included in the primary research question, categorised as either fully qualitative or mixed methods [ 18 21 , 23 29 ]. Additional searches for solely qualitative studies resulted in an additional 6 relevant papers being identified (Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 12 articles, almost half (n = 5) [40][41][42][43][44] of the retrieved articles have illustrated cooking classes as part of a self-care or mindfulness programme; however, mindfulness was not clearly incorporated into the cooking classes. These studies embraced the idea of teaching kitchens [40][41][42].…”
Section: Cooking and Mindfulness In Self-care Programmesmentioning
confidence: 99%
“…Thompson and his team [44] have also adopted a similar programme called the Meals, Mindfulness and Moving Forward (M3) lifestyle programme, which involves the same content but aims to achieve different psychological outcomes, such as self-efficacy and resilience through self-care activities. Cooking was coded to the same psychological themes as mindfulness, mainly self-efficacy and behavioural changes, even though mindfulness was coded to most psychological themes.…”
Section: Cooking and Mindfulness In Self-care Programmesmentioning
confidence: 99%